The paradigm on the open source project management tools / Mohd Nuruddin Hurairah Mansor - Mansor, Mohd Nuruddin Hurairah (2005)
Although IT is becoming more reliable, faster and less expensive, the cost, complexities, and risk of IT project continue to increase. When relates to the project management studies, IT has been accepted as one of the core substance in accomplishing this subject. Defined as both a process and set of tools and techniques concerned with defming the project's goal, planning all the work to reach the goal, leading the project and support teams, monitoring progress, and seeing to it that the project is completed in a satisfactory way, tools plays a crucial and beneficial role in it. Project management could be tedious and demanding. This is where project management tools play its roles. Divided into two categories, the open source project management tools and proprietary project management tools, each having its advantage over one another. This research will try to identify types of open source project management tools and its application. It will also try to propose solutions to project management tools using open source approach which is considered the most applicable replacement for the proprietary tools and lastly the research will try to recognize the significance between the open source and proprietary project management tools